2001
DOI: 10.1152/ajpregu.2001.280.4.r1116
|View full text |Cite
|
Sign up to set email alerts
|

The functional regeneration of syncytiotrophoblast in cultured explants of term placenta

Abstract: We have investigated the functional characteristics of term human placental villous explants kept in long-term (7-11 days) culture. Fragments of placental villous tissue (approximately 5-10 mg wet wt) were cultured in supplemented CMRL-1066 culture medium for up to 11 days. After the first day of culture, the syncytiotrophoblast appeared vacuolated and eventually degenerated. However, a new syncytiotrophoblast developed by day 4, being indistinguishable from that of a fresh placenta by 11 days. Release of huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
110
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(136 citation statements)
references
References 29 publications
25
110
1
Order By: Relevance
“…Basic studies on placental villous explant viability; analysis of morphology, metabolic activity, glucose consumption, lactate production and protein expression have shown that placental explants remain functional for ~2 weeks following an initial degeneration with recovery after ~48 h of culture [62,63]. A detailed understanding of the extent to which placental explant integrity is comparable to the physiological, in vivo situation and how the process of post-ischemic recovery in vitro affects tissue integrity and viability is lacking [62][63][64].…”
Section: Human Placental Explantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Basic studies on placental villous explant viability; analysis of morphology, metabolic activity, glucose consumption, lactate production and protein expression have shown that placental explants remain functional for ~2 weeks following an initial degeneration with recovery after ~48 h of culture [62,63]. A detailed understanding of the extent to which placental explant integrity is comparable to the physiological, in vivo situation and how the process of post-ischemic recovery in vitro affects tissue integrity and viability is lacking [62][63][64].…”
Section: Human Placental Explantsmentioning
confidence: 99%
“…A detailed understanding of the extent to which placental explant integrity is comparable to the physiological, in vivo situation and how the process of post-ischemic recovery in vitro affects tissue integrity and viability is lacking [62][63][64]. In particular, the significance of the interval between delivery and initiation of explant culture is poorly understood.…”
Section: Human Placental Explantsmentioning
confidence: 99%
“…As regards cellular homeostasis, Birdsey et al, (1999) showed that hypoosmotic challenge of the syncytiotrophoblast resulted in activation of both K + , and anion, conductances (Birdsey et al, 1999) suggesting that they are involved in maintenance of cell volume. K + efflux is also stimulated by angiotensin and ATP, and there is evidence that the latter effects specifically the Ca 2+ sensitive K + channels (Clarson et al, 2002;Siman et al, 2001). In relation to regulation of secretory processes, recent data show that specific K + channel blockers inhibit the secretion of human chorionic gonadotrophin from syncytiotrophoblast (Williams et al, 2007).…”
Section: Potassium Channelsmentioning
confidence: 99%
“…40 All reagents, unless otherwise indicated, were purchased from Sigma-Aldrich Ltd. (Oakville, ON, Canada).…”
Section: Reagents and Solutionsmentioning
confidence: 99%